Decision Making Concept: The Role Of Educational Leadership In Determining Policies - Nur Ali (CV. Akira Java Bulu, 2025)
This study aims to analyze the concept of decision-making in educational leadership through a literature review approach. Decision-making is a crucial process in carrying out leadership functions, especially within the dynamic and complex context of educational institutions. Using a qualitative approach and library research method, this study examines various academic literatures discussing definitions, types, and approaches to decision-making. The findings indicate that decision-making in educational leadership is not merely technical, but also involves ethical, collaborative, and strategic considerations. Several approaches can be utilized by educational leaders, such as rational, intuitive, participative, and contingency approaches. Each approach has its own characteristics and applications depending on the organizational context, school culture, and the situation at hand. This study is expected to contribute to the development of leadership insights and serve as a reference for educational practitioners in managing institutions effectively.